2018
DOI: 10.1039/c8cc06106h
|View full text |Cite
|
Sign up to set email alerts
|

Choline-mediated synthesis of zeolite ERS-7 via an excess fluoride approach

Abstract: A high-silica (Si/Al = 14) version of zeolite ERS-7 has been synthesized using choline as an organic structure-directing agent (OSDA) via an excess fluoride approach, and the physicochemical properties of this cage-based small-pore material and its catalytic and adsorption properties are evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…FER is calculated to be the preferred zeolite phase with a synthesis energy of −1.008 eV/TO 2 followed closely by RUT ( E syn = −0.999 eV/TO 2 ). This is in accordance with the experimental study of Bae et al where FER and RUT are the synthesis products at lower fluoride concentrations when SDA4 is utilized in aluminosilicate media, with FER being the main product (Table ). In fact, Lee et al also stated that RUT was always obtained as an impurity using SDA4 with a very small amount of Na + present.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…FER is calculated to be the preferred zeolite phase with a synthesis energy of −1.008 eV/TO 2 followed closely by RUT ( E syn = −0.999 eV/TO 2 ). This is in accordance with the experimental study of Bae et al where FER and RUT are the synthesis products at lower fluoride concentrations when SDA4 is utilized in aluminosilicate media, with FER being the main product (Table ). In fact, Lee et al also stated that RUT was always obtained as an impurity using SDA4 with a very small amount of Na + present.…”
Section: Resultsmentioning
confidence: 99%
“…Since this information is not present in the experiments reported in Table , we do not have, currently, enough information to try to explain why the calculated synthesis energy of ESV is higher than that of AST in the aluminosilicate composition (Table ). Nevertheless, the experiments at HF/SDA = 1.0 indicate (Table 1 of ref ) that AST was obtained at Si/Al = 20, hence hinting that this phase could also be obtained at HF/SDA = 1.5 and Si/Al ca. 9, according to our prediction.…”
Section: Resultsmentioning
confidence: 99%
“…40,[74][75][76] The excess fluoride approach (HF/OSDA = 2) also allowed them to synthesize a high-silica (Si/ Al = 14) version of zeolite ERS-7 (ESV) using choline (Ch + ) ions. 77 Considering the unit cell composition and multinuclear MAS NMR results, they suggested that some F À anions paired with Ch + located within large 17-hedral ([4 6 5 4 6 5 8 2 ]) picnicbasket-shaped cages make the resulting zeolite more siliceous.…”
Section: Fluoride Anions As An Inorganic Synthesis Parametermentioning
confidence: 99%
“…Despite its simplicity, choline, when used together with various alkali and/or alkaline earth metal cations, can direct the synthesis of more than 10 different zeolite structures, many of which are different from those crystallized in the presence of TMA + or TEA + . We recently synthesized a high-silica (Si/Al = 14) version of zeolite ERS-7 (ESV) using this OSDA in excess fluoride conditions (HF/OSDA = 2.0) . Given that choline gave other phases like ferrierite when HF/OSDA ≤ 1.0, the excess fluoride approach may be a valuable tool to obtain zeolites with known framework structures but new compositions.…”
Section: Excess Fluoride Approachmentioning
confidence: 99%
“…37 We recently synthesized a high-silica (Si/Al = 14) version of zeolite ERS-7 (ESV) using this OSDA in excess fluoride conditions (HF/OSDA = 2.0). 38 Given that choline gave other phases like ferrierite when HF/OSDA ≤ 1.0, the excess fluoride approach may be a valuable tool to obtain zeolites with known framework structures but new compositions. We also note that, like as-made PST-21 and PST-22, the F − content in our high-silica ERS-7, although synthesized in the presence of a large concentration of this anion, is not so high.…”
Section: High-silica Ers-7mentioning
confidence: 99%